Draft Annual Plan 1989-90 State Planning Commission - Planning Commission (Planning Commission, 1989)
Being the terminal year, the annual plan for 1989-90 assumes significance. In the formulation of this plan we have been guided by two principal considerations, viz., (i) the plan efforts should help in consolidating the gains realised in the earlier years, make up for the deficiencies observed and try to build a good base, from which the Eighth Plan could take off smoothly, and (ii) keeping the plan size at a reasonable level which would ensure that the growth process is sustained but which will not be oblivious to the resource constraint the State is placed in. Our discussions with the representatives of the various development departments had a special focus on these issues. No new schemes have been included for the year 1989-90, highest priority has been accorded to the on-going schemes— bringing some to a successful fruition and continuing others without impairing their implementation efficiency for lack of funds. The plan size arrived at is Rs. 12,43.00 crores.
Draft Annual Plan 1989-90
Government of Tamil Nadu